Early response assessment of glioma patients to definitive chemoradiotherapy using chemical exchange saturation transfer imaging at 7 T - Meißner, Jan-Eric; Regnery, Sebastian; Floca, Ralf; Debus, Jürgen; Schlemmer, Heinz-Peter; Ladd, Mark E.; Bachert, Peter; Adeberg, Sebastian; Paech, Daniel (Journal of magnetic resonance imaging, 2019)
Background Patients with newly diagnosed inoperable glioma receive chemoradiotherapy (CRT). Standard Response Assessment in Neuro-Oncology (RANO) takes a minimum of 4 weeks after the end of treatment. Purpose/Hypothesis To investigate whether chemical exchange saturation transfer (CEST) MRI enables earlier assessment of response to CRT in glioma patients. Study Type Longitudinal prospective study. Population Twelve brain tumor patients who underwent definitive CRT were included in this study. Three longitudinal CEST MRI measurements were performed for each patient at 7T: first before, second immediately after completion of CRT, and a third measurement as a 6-week follow-up. Field Strength/Sequence Conventional MRI (contrast-enhanced, T2w and diffusion-weighted imaging) at 3T and T2w and CEST MRI at 7T was performed for all patients. Assessment The mean relaxation-compensated relayed nuclear-Overhauser-effect CEST signal (rNOE) and the mean downfield-rNOE-suppressed amide proton transfer (dns-APT) CEST signal were investigated. Additionally, choline-to-N-acetyl-aspartate ratios (Cho/NAA) were evaluated using single-voxel 1H-MRS in six of these patients. Performance of obtained contrasts was analyzed in assessing treatment response as classified according to the updated RANO criteria. Statistical Test Unpaired Student's t-test. Results The rNOE signal significantly separated stable and progressive disease directly after the end of therapy (post-treatment normalized to pre-treatment mean ± SD: rNOEresponder = 1.090 ± 0.110, rNOEnon-responder = 0.808 ± 0.155, P = 0.015). In contrast, no significant difference was observed between either group when assessing the normalized dns-APT (dns-APTresponder = 0.953 ± 0.384, dns-APTnon-responder = 0.972 ± 0.477, P = 0.95). In the smaller MRS subcohort, normalized Cho/NAA decreased in therapy responders (Cho/NAAresponder = 0.632 ± 0.007, Cho/NAAnon-responder = 0.946 ± 0.124, P = 0.070). Data Conclusion rNOE mediated CEST imaging at 7T allowed for discrimination of responders and non-responders immediately after the end of CRT, additionally supported by 1H-MRS data. This is at least 4 weeks earlier than the standard clinical evaluation according to RANO. Therefore, CEST MRI may enable early response assessment in glioma patients. Level of Evidence: 1 Technical Efficacy Stage: 5 J. Magn. Reson. Imaging 2019;50:1268-1277.